Predictability of a New Orthodontic Extrusion Technique for Implant Site Development: A Retrospective Consecutive Case-Series Study. (25th January 2020) - Conserva, E.; Fadda, M.; Ferrari, V.; Consolo, U.
Abstract : In clinical daily practice, there are situations in which implant sites have vertical and/or horizontal bone defects and often we must improve their morphology and dimensions before fixture insertion. It is crucial to carefully evaluate the surgical site as regards the characteristics of both hard and soft tissues. The orthodontic extrusion technique can be used for nonsurgical augmentation of the implant site as an alternative to traditional regenerative/reparative surgical therapies. The orthodontic extrusion is based on a biological mechanism that uses the portion of periodontal ligament, still present on the root before the tooth extraction, for the increase of hard and soft tissues. In the literature, there is no evidence of common guidelines for this technique but only tips based on personal experience and/or previous studies. The aim of this study was to investigate and to validate the reliability of a new orthodontic extrusion technique (MF Extrusion Technique, by Dr. Mauro Fadda) by means of a retrospective consecutive case-series study. After we have done a review of the literature, we evaluated the X-rays of twelve consecutively treated patients before the orthodontic extrusion (T0) and after the stabilization period (T1), in order to quantify, by two different measurements, area and linear, the bone gain obtained by the application of the new technique. All the patients examined showed a significant increase in bone areas with an average value of 31.575 mm 2 . The linear bone gain had an average value of 4.63 mm. Data collected were statistically analysed by the Wilcoxon signed-rank test. The results obtained both from area and linear measurements at T0 and at T1 times showed that there was a statistically significant bone gain with p < 0.01 .